PENGARUH DISIPLIN KERJA, MOTIVASI DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI BADAN PEMBERDAYAAN PEREMPUAN DAN KELUARGA BERENCANA DAERAH (BPPKBD) PROVINSI SULAWESI TENGAH - Pradipta, Teguh Ananta (Katalogis, 2017)
The study is aimed to explore simultaneous and partial influences of work discipline, motivation, and career development on officials’ performance in the Agency of Women Empowerment and Family Oplanning in Central Sulawesi. Type of research is desciptive causal. As many 60 respondents werre selected through census method. Instrumen of data collection is questionnaire and method of analysis is multiple linear regressions. The results concludes that work discipline, motivation, and career development simultaneously and partially have positive and significant influence on officials’ performance in The Agency Of Women Empowerment And Family Planning In Central Sulawesi.